On the scientific basis for developing rural development strategies - A. I. Kostyaev (Аграрная наука Евро-Северо-Востока, 2020)
The article presents the results of the systematization of the scientific foundations for developing rural development strategies. The theory, methodology and methods of solving this problem have been merged into a single whole. Grouping of the scientific aspects of strategies in the context of key issues of their development is given. The choice of the paradigm of rural development is justified. In relation to the development of rural territories, the essence of the concept of “strategy” is formulated. The definition of the essence of the strategy reflects multifunctionality, goals and objectives, resource potential and the socio-economic environment for the development of rural areas. The approaches to assessing the conditions and factors of endogenous rural development are established. To evaluate internal and external factors, it is recommended to use SWOT analysis, for external ones - PEST analysis. The methods of goal-setting and assessment of priorities in solving the problems of rural development are proposed. Targeting is recommended based on the decomposition of the general goal of the strategy. The general goal is defined as the transition of rural territories from an exogenous to an endogenous path of development while increasing the competitiveness of the rural economy and increasing the quality of life of the rural population. The set of strategic goals and objectives in the strategy is proposed to be directed to the restructuring of the development of rural areas with a focus solely on the dominance of external support to the maximum possible use of internal potential. It is recommended that prioritization of the solution of tasks to achieve the general goal of the strategy be carried out by the method of expert evaluations using the constructed “goal tree”. It is proposed to build the mechanism for the implementation of strategies within the framework of the paradigm of endogenous development of rural territories on the widespread use of “rural networks”. Networks in this case are considered as a hybrid form of coordination of the development of rural areas lying between the hierarchy and the market.